Modeling data mart using ETL (extract, transform, load) webservice concept on feeder with a dashboard - Hermawan, Aditiya; Kurnia, Yusuf; Destiandi, Niki; Kurnaedi, Didi (International Journal of Engineering and Technology, 2019)
College in Indonesia do reporting students, lecturers, and lecture activities data to PDDIKTI (Bahasa: Pangkalan Data Pendidikan Tinggi/ Higher Education Database). FEEDER PDDIKTI doesnâ€™t have any measurement components such as KPI (Key Performance Indicator) which can be used for measure performance and evaluation of academic activities at college. Problem that occur there is a lot of academic data stored but when transform it to a report at the time of academic activities evaluation becomes difficult and takes a long time and requires a monitoring, evaluating and measuring tools that can be measure performance of the college. Data mart modeling using star schema bring through to analyze data from various perspectives according to the number of dimensions. Academic data within data mart sourced from FEEDER PDDIKTI after going through the ETL (Extract Transform Load) process by using web service then visualized into graphic form on the dashboard which there is a KPI inside to measure performance at college. Dashboard with KPI inside that has been built providing convenience in conducting analysis, monitoring and evaluation of academic activities with the level of user satisfaction achieved by 82%.Â